Perhitungan Unit Cost Akomodasi Rawat Inap Bangsal Kelas Iii Ruang Arofah Dengan Metode Activity Based Costyng System Pada Rsu Pku Muhamadiyah Yogyakarta - Mahfud, Mahfud (Universitas Muhammadiyah Yogyakarta, 2014)
Hospitals now growing and developing, need managed efficiently and effectively, it is necessary to face the tough competition in the health world. PKU Muhammadiyah Hospital of Yogyakarta to the unit cost Arofah Ward III class space using traditional accounting system in determining the cost of hospitalization rates. Goal : The goal of this study to determine the calculation and determine the level of unit cost inpatient ward accommodation space Arofah class III RS PKU Muhammadiyah and compare the unit cost is determined management of PKU Muhammadiyah Hospital of Yogyakarta. Methods: The study was descriptive qualitative research. The instruments used are owned financial documentation guidelines hospital. Cost analysis method used is based ABC (Activity Based Costing) system. Results: The results using Activity Based Costing (ABC) is Rp 49.237, unit cost incurred hospital Rp 75.000. ABC method gives lower results. With the difference, Rp.25.763. Differences occur, due to the overhead of loading on each product. Conclusion: Calculation of unit cost approach to Activity Based Costing (ABC) is more effective and efficient when used for the calculation value is smaller than the unit cost imposed by the hospital so that patients do not need to pay cost sharing.